AN ANALYSIS OF DISTANCE LEARNING IMPLEMENTATION DURING THE PANDEMIC IN TEACHING ENGISH - Yusika Wulandari; Thomas Joni Verawanto Aristo (INOVISH JOURNAL, 2022)
The background of this research is the application of distance learning in learning English.  This study aims 1) To describe the process of implementing distance learning in learning English at SMPN 02 Kayan Hilir during the Covid-19 pandemic.  2) To find out the obstacles to implementing distance learning to teach English at SMPN 02 Kayan Hilir during the Covid-19 pandemic.  3) To find out the impact of implementing distance learning for teaching and English at SMPN 02 Kayan Hilir during the Covid-19 pandemic.  The research method used is qualitative research.  The results showed that the implementation of distance learning in learning English for class VIII students at SMPN 02 Kayan Hilir had been implemented well despite the obstacles and impacts 06.25 from distance learning for schools and English teachers and students have a solution.  Based on the results of the study, it can be concluded that in the learning process, the obstacles and impacts of implementing distance learning based on whatsapp and how teachers overcome obstacles and impacts have their respective solutions so that English language learning can be carried out properly. Keywords:Distance Learning, Distance Learning Implementation, English Teaching